Married Women, Testaments and Property in Sixteenth-Century Scotland. Issue 1 (April 2023) - Beattie, Cordelia; Spence, Cathryn
Abstract : This article responds to the debate about married women's legal position in pre-modern Scotland and how it compared with neighbouring countries, particularly whether married women could own property and of what that might consist. While many studies centre theoretical discussions and focus on the seventeenth century onwards, this article centres sixteenth-century records of practice by appraising the 14, 664 testamentary documents that survive in court registers in the National Records of Scotland. The study of these records reveals that testaments made by married women outnumber those made by widows (having verified, for example, that those women indexed as 'sometime spouse' were married at the time of death). The nature of these records, which include inventories as well as last wills, allows insight into the material household and married women's role in the ownership and disposal of this property. The article demonstrates that many married women claimed more than paraphernalia (clothing and jewellery) and that some even tried to give away more than the third or half share routinely allocated to them. It also finds clear references to property being held in common.